High‐Performance Non‐Enzyme Hydrogen Peroxide Detection in Neutral Solution: Using a Nickel Borate Nanoarray as a 3D Electrochemical Sensor. Issue 64 (23rd October 2017) - Wang, Zao; Xie, Fengyu; Liu, Zhiang; Du, Gu; Asiri, Abdullah M.; Sun, Xuping
Abstract: It is highly attractive to construct natural enzyme‐free nanoarray architecture as a 3D catalyst for hydrogen peroxide detection due to its great specific surface area and easy accessibility to target molecules. In this communication, we demonstrate that nickel borate nanoarray supported on carbon cloth (Ni−Bi/CC) behaves as an efficient catalyst electrode for H2 O2 electro‐reduction in neutral media. As a non‐enzymatic electrochemical H2 O2 sensor, such Ni−Bi/CC shows superior sensing performances with a fast response time (less than 3 s), a low detection limit (0.85 nm, S/ N =3), and a high sensitivity (18320 μA mm  cm −2 ). Importantly, it also demonstrates favourable reproducibility and long‐term stability. Abstract : A nickel borate nanoarray on carbon cloth (Ni−Bi/CC) behaves as an efficient catalyst electrode for H2 O2 electroreduction in neutral media. As a non‐enzymatic electrochemical H2 O2 sensor, such Ni−Bi/CC shows superior sensing performances with a fast response time (less than 3 s), a low detection limit (0.85 nm, S / N =3), and a high sensitivity (18320 μA mm  cm −2 ).